A Barley Efflux Transporter Operates in a Na+-Dependent Manner, as Revealed by a Multidisciplinary Platform. Issue 1 (15th December 2015) - Nagarajan, Yagnesh; Rongala, Jay; Luang, Sukanya; Singh, Abhishek; Shadiac, Nadim; Hayes, Julie; Sutton, Tim; Gilliham, Matthew; Tyerman, Stephen D.; McPhee, Gordon; Voelcker, Nicolas H.; Mertens, Haydyn D.T.; et al.
Abstract : A barley efflux transporter that is primarily borate-permeable operates as a channel in a Na + -dependent manner. Abstract: Plant growth and survival depend upon the activity of membrane transporters that control the movement and distribution of solutes into, around, and out of plants. Although many plant transporters are known, their intrinsic properties make them difficult to study. In barley ( Hordeum vulgare ), the root anion-permeable transporter Bot1 plays a key role in tolerance to high soil boron, facilitating the efflux of borate from cells. However, its three-dimensional structure is unavailable and the molecular basis of its permeation function is unknown. Using an integrative platform of computational, biophysical, and biochemical tools as well as molecular biology, electrophysiology, and bioinformatics, we provide insight into the origin of transport function of Bot1. An atomistic model, supported by atomic force microscopy measurements, reveals that the protein folds into 13 transmembrane-spanning and five cytoplasmic α-helices. We predict a trimeric assembly of Bot1 and the presence of a Na + ion binding site, located in the proximity of a pore that conducts anions. Patch-clamp electrophysiology of Bot1 detects Na + -dependent polyvalent anion transport in a Nernstian manner with channel-like characteristics. Using alanine scanning, molecular dynamics simulations, and transport measurements, we show that conductance by Bot1 is abolished by removal of the Na + ion binding site. Our data enhance the understanding of the permeation functions of Bot1.